Intermittent Fasting Modulation of the Diabetic Syndrome in Streptozotocin-Injected Rats - Louiza Belkacemi; Ghalem Selselet-Attou; Emeline Hupkens; Evrard Nguidjoe; Karim Louchami; Abdullah Sener; Willy J. Malaisse (International Journal of Endocrinology)
This study investigates the effects of intermittent overnight fasting in streptozotocin-induced diabetic rats (STZ rats). Over 30 days, groups of 5-6 control or STZ rats were allowed free food access, starved overnight, or exposed to a restricted food supply comparable to that ingested by the intermittently fasting animals. Intermittent fasting improved glucose tolerance, increased plasma insulin, and lowered Homeostatis Model Assessment index. Caloric restriction failed to cause such beneficial effects. The β-cell mass, as well as individual β-cell and islet area, was higher in intermittently fasting than in nonfasting STZ rats, whilst the percentage of apoptotic β-cells appeared lower in the former than latter STZ rats. In the calorie-restricted STZ rats, comparable findings were restricted to individual islet area and percentage of apoptotic cells. Hence, it is proposed that intermittent fasting could represent a possible approach to prevent or minimize disturbances of glucose homeostasis in human subjects.